Measuring the Effects of Financial and Economic Shocks on Some Macro Variables in Some Developing Countries - Muaamal Hussein Jwesim; Ghufran Shallal Mohammed (Harmoni Economics: International Journal of Economics and Accounting, 2024)
This research attempted to analyze the impact of financial and economic shocks in a number of developing countries that are similar in terms of the size of the economy and the diversity of its economic structure, as well as the similarity in the quality of the exchange systems used to demonstrate the extent of the monetary authorities’ ability to target inflation in light of the occurrence of shocks of various types and forms during the research period, in addition to This is an indication of the extent of the diversity of the economy and its connection to those shocks, as the oil sector constitutes a large portion of the gross domestic product of the countries of the research sample, with this being lower for the Emirati economy, and this matter made the Iraqi economy to be more affected by the economic crises and shocks that occurred during the period of the study compared to other economies. Saudi Arabia and the Emirates, where the Saudi economy comes in second place in terms of being affected by these shocks, followed by the Emirati economy, which had the least impact. The research variables (inflation, public revenues, and gross domestic product) were also closely linked to the occurrence of both positive and negative financial and economic shocks. When countries face a positive economic shock, the economic situation in the sample countries improves, and the research variables tend to increase, and vice versa when those countries face a shock. Negative, taking into account the varying rates of impact and response, especially with the UAE economy.